Galileo's leaning tower experiment : a science adventure - Macdonald, Wendy (Wendy Margaret); Rui, Paolo (Watertown, MA : Charlesbridge, 2009)
Galileo, having observed a young boy dropping food from a bridge into his uncle's boat, conducts several experiments to study gravity.
Wilson's Children, October 2010
School Library Journal, June 2009
Booklist, February 2009
Horn Book, October 2009
Kirkus Review, January 2009
Library Media Connection, October 2009
Keywords: Mathematical physics -- Juvenile literature; Gravity -- Juvenile literature; Galilei, Galileo, -- 1564-1642 -- Juvenile literature; Physics; Mathematics; Gravity; Galileo, -- 1564-1642.; Physics; Mathematics; Gravity; Galileo, -- 1564-1642.